Viticulture for better prospects - Upadhyay, K; Saha, Sujoy; Yadav, D S; Sharma, A K; T P, Ahammed Shabeer; Upadhyay, Anuradha; Somkuwar, R G (Indian Horticulture, 2022)
Grape, a temperate crop, has been adopted to tropical conditions in India, and most of the area under grape cultivation is in peninsular Indian states, viz. Maharashtra, Karnataka, and Tamil Nadu. The viticultural practices involve double pruning (foundation and fruit pruning) and single cropping to make the grapevines yield under tropical conditions. The area under grapes in India has increased from 52.1 thousand ha (2002-03) to 139 thousand ha (2018-19) (NHB Database), a 2.6 folds increase in 15 years. The production during the corresponding period has increased by 2.38 times. The grape is highly skilled, heavy investment prone and high-value crop. However, in recent years, extreme weather events like hail, unseasonal rainfall, frost, delayed rainfall and temperature stress during the productive period are playing havoc with the grapevine production in India. These factors pose challenges to researchers to develop technologies and/or strategies for sustainable grape cultivation.